Democratic Party Candidates for Delegates to Party National Convention (1976)
This document is an official Democratic Party list of candidates for delegate positions to the 1976 Democratic National Convention, organized by congressional district and presidential candidate preference. It covers the June 8, 1976 California consolidated primary election and is presented in both English and Spanish. The delegates are pledged to various candidates, including Edmund G. Brown Jr., Jimmy Carter, Frank Church, Fred R. Harris, Henry Jackson, Ellen McCormack, Morris Udall, and George Wallace. For each congressional district, the names of individuals running as pledged delegates are provided, while some districts list no candidates for certain campaigns. Overall, the document serves as a comprehensive ballot guide identifying delegate slates by candidate and district.